Forecasting Maize Production in Telangana State Using Arima Model - , M. Maheshnath, R. Vijaya Kumari, K. Suhasini, D. Srinivasa Reddy, A. Meena (Archives of Current Research International, 2024)
The study utilized the Box-Jenkins approach for forecasting maize production in Telangana state. It involved the analysis of 55 years of empirical annual observations of maize production. The autocorrelation (ACF) and partial autocorrelation functions (PACF) were calculated to analyze the data. A suitable Box-Jenkins ARIMA model was fitted, and the validity of the model was examined using conventional statistical methods. Lastly, the next three years' worth of maize production was predicted using the autoregressive integrated moving average model's forecasting capability.